Edukasi kesehatan imunisasi Measles Rubella menggunakan video animasi dan pesan teks melalui WhatsApp - Yunita Andriani; Kusnandi Rusmil; Ieva Baniasih Akbar (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: This study aimed to compare the effect of health education using animated video and text messages through WhatsApp on parental knowledge and attitude. Method: This study used a quasi-experimental design on two groups that consisted of 36 respondents in each group. The first group received animation videos about MR immunization, and the second group received text messages through WhatsApp. The instruments of this study consisted of a knowledge questionnaire and an attitude questionnaire. The study was conducted on parents who had an infant less than nine months old, had a smartphone and WhatsApp account. Results: The pretest-posttest scores show increased knowledge and attitude about MR immunization after educational animation video and text message intervention. Video animation had a higher mean of knowledge and attitude than text messages. Conclusion: Health education using animation videos through WhatsApp can improve parental knowledge and attitude higher than a text message.